Stochastic Complementarity - Paola Manzini; Marco Mariotti; Levent Ülkü (Institute of Labor Economics (IZA), 2018)
The Hicksian definition of complementarity and substitutability may not apply in contexts in which agents are not utility maximisers or where price or income variations, whether implicit or explicit, are not available. We look for tools to identify complementarity and substitutability satisfying the following criteria: they are behavioural (based only on observable choice data); model-free (valid whether the agent is rational or not); and they do not rely on price or income variation. We uncover a conflict between properties that it is arguably reasonable for a complementarity notion to possess. We discuss three different possible resolutions of the conflict.
Keywords: D0; 330; complements and substitutes; correlation; stochastic choice